Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11427-015-4961-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and comparative analysis of root transcriptomes from different varieties of Panax ginseng C. A. Meyer grown in different environments

Abstract: Panax ginseng C. A. Meyer is an important traditional herb in eastern Asia. It contains ginsenosides, which are primary bioactive compounds with medicinal properties. Although ginseng has been cultivated since at least the Ming dynasty to increase production, cultivated ginseng has lower quantities of ginsenosides and lower disease resistance than ginseng grown under natural conditions. We extracted root RNA from six varieties of fifth-year P. ginseng cultivars representing four different growth conditions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In the study by Chen et al (2019), the average contents of ginsenosides indicated that the distinct volcanic pumice soil conditions of New Zealand might be more suitable for ginseng cultivation than original native locations (China and Korea) [36]. Different ginseng processing methods and cultivation environments [37] may be required due to variations in the amounts of ginsenosides [38].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Chen et al (2019), the average contents of ginsenosides indicated that the distinct volcanic pumice soil conditions of New Zealand might be more suitable for ginseng cultivation than original native locations (China and Korea) [36]. Different ginseng processing methods and cultivation environments [37] may be required due to variations in the amounts of ginsenosides [38].…”
Section: Resultsmentioning
confidence: 99%
“…Sathiyamoorthy et al [23] firstly reported comparative transcriptome analyses of FCG and MCG, and preliminarily discussed putative isoprenoids pathways based on 6757 expressed sequence tags from hairy roots and roots of 14-year-old MCG and 4-year-old FCG. Zhen et al [24] built a set of root transcriptomes from three types of ginseng roots (i.e., roots of FCG, MCG and wild ginseng), and found that three genes encoding key terpenoids biosynthesis enzymes including HMGCR, MVK and SE were more active in wild ginseng root than in FCG’s. Wang et al [25] identified 78 genes of 13 enzymes from roots of 5-, 12-, 18- and 25-year-old MCG and 4-year-old FCG involved in biosyntheses of terpenoids backbone and triterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…China is vast in territory and the majority of herbs have more than one place of origin. Herbs in different districts and growth condition vary in effective composition content that is responsible for the otherness in curative effect ( 13 ). Lack of stable quality control in herbs still blocks the way of TCM modernization.…”
Section: Introductionmentioning
confidence: 99%